Host immunity modulates the efficacy of microbiota transplantation for treatment of Clostridioides difficile infection - Eric R. Littmann (Nature Portfolio, 2021)
Transfer of a host’s microbiota by faecal microbiota transplantation has shown benefit in the context of recurrent Clostridioides difficle infection. Here the authors shows the inflammatory status of the recipient can impact on engraftment and the efficacy of the introduced microbiota in a model of C.difficile infection.